Um roteiro de leitura possível para o Fundo Documental Aldema Menini Mckinney - Knackfuss, Caroline Lopes (2020)
This dissertation seeks to reflect on the possibility of different ways of reading and interpreting the archive, represented by the Aldema Menini Mckinney Documentary Fund (FDAMM). We understand that currently several researches are focused on the importance of preserving documents and collections of researchers in Documentation Centers and Documentary Funds and have gained more and more notoriety with UFSM starting, mainly, from the creation of projects that aim to preserve a memory discipline that helps us to reflect on the knowledge production process. One of these projects is the Documentation and Memory Center (CDM), which houses, so far, three Documentary Funds and one Collection, namely: Neusa Carson Documentary Fund, Aldema Menini Mckinney Documentary Fund, Maria Luiza Ritzel Remédios Documentary Fund and the Collection Michael Phillips. Supported by the theoretical perspective of the Discourse Analysis of the French line, this study seeks to articulate some reflections with Archivology, especially with regard to the concept of Archive. Making a description of the process of constituting the FDAMM, elaborating the arrangement framework, to reflect on the constitution of the gestures of interpretation that constitute the Documentary Fund, we also rely on archival assumptions to build our objectives, that is, to reflect on the constitution of this Documentary Fund, especially on the gestures of interpretation (of the subject-holder and the subjectarchivist, above all) that permeate the process of donation, selection, organization and elaboration of the arrangement framework made available to future researchers and other interested parties. In this way, we offer the reader a possible reading guide to enter the FDAMM, alerting him of the possible pitfalls of the file and of the interpretation gestures that the file carries. We show the behind the scenes of the constitution of a Documentary Fund, considering the importance of the processes and also of the subjects involved. So we hope that the study developed can contribute to advancing research on the importance of Documentation Centers and Documentary Funds, as well as establishing a dialogue with different areas of knowledge, especially with regard to the preservation of memory and the disciplinary constitution. Key